AgKit4EE: A toolkit for agricultural land use modeling of the conterminous United States based on Google Earth Engine. (July 2020) - Zhang, Chen; Di, Liping; Yang, Zhengwei; Lin, Li; Hao, Pengyu
Abstract: Google Earth Engine (GEE) is an ideal platform for large-scale geospatial agricultural and environmental modeling based on its diverse geospatial datasets, easy-to-use application programming interface (API), rich reusable library, and high-performance computational capacity. However, using GEE to prepare geospatial data requires not only the skills of programming languages like JavaScript and Python, but also the knowledge of GEE APIs and data catalog. This paper presents the AgKit4EE toolkit to facilitate the use of the Cropland Data Layer (CDL) product over the GEE platform. This toolkit contains a variety of frequently used functions for use of CDL including crop sequence modeling, crop frequency modeling, confidence layer modeling, and land use change analysis. The experimental results suggest that the proposed software can significantly reduce the workload for modelers who conduct geospatial agricultural and environmental modeling with CDL data as well as developers who build the GEE-enabled geospatial cyberinfrastructure for agricultural land use modeling of the conterminous United States. AgKit4EE is an open source and it is free to use, modify, and distribute. The latest release of AgKit4EE can be imported to any modeling workflow developed using GEE Code Editor (https://code.earthengine.google.com/?accept_repo=users/czhang11/agkit4ee ). The source code, examples, documentation, user community, and wiki pages are available on GitHub (https://github.com/czhang11/agkit4ee ). Highlights: The use of Cropland Data Layer product on Google Earth Engine is significantly simplified. Frequently used geospatial modeling functions for Cropland Data Layer are implemented. New agricultural land use products, such as crop rotation map and crop frequency map, are derived. Web-based prototypes for agricultural land use modeling are published as Earth Engine Apps.